2018
DOI: 10.1097/rli.0000000000000419
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Unenhanced T1-Weighted Signal Intensities Within the Dentate Nucleus and the Globus Pallidus After Serial Applications of Gadopentetate Dimeglumine Versus Gadobutrol in a Pediatric Population

Abstract: The T1-weighted SI increase within the DN and GP after serial administrations of the linear contrast medium gadopentetate dimeglumine, but not after serial applications of the macrocyclic agent gadobutrol, found in a pediatric population, is consistent with results published for adult patients. The clinical impact of the intracranial T1-hyperintensities is currently unclear. However, in accordance with the recent decision of the Pharmacovigilance and Risk Assessment Committee of the European Medicines Agency, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
20
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 64 publications
3
20
1
Order By: Relevance
“…Our study also revealed a good correlation between the number gadoterate meglumine administrations and the T 1 W SI increase for the DN, pons, GP, and T as well. Many studies used pons or thalamus as a reference anatomical location for standardization and dentate nucleus‐to‐pons or thalamus, GP‐to‐pons or thalamus ratios were assessed and compared . However, in the current study the T 1 W SI of both the pons and thalamus were also found to be increased compared with those of the control group.…”
Section: Discussioncontrasting
confidence: 62%
See 1 more Smart Citation
“…Our study also revealed a good correlation between the number gadoterate meglumine administrations and the T 1 W SI increase for the DN, pons, GP, and T as well. Many studies used pons or thalamus as a reference anatomical location for standardization and dentate nucleus‐to‐pons or thalamus, GP‐to‐pons or thalamus ratios were assessed and compared . However, in the current study the T 1 W SI of both the pons and thalamus were also found to be increased compared with those of the control group.…”
Section: Discussioncontrasting
confidence: 62%
“…Bhargava et al reported that there was no increased SI in the GP or DN with the use of at least five doses of gadobutrol, a macrocyclic GBCA. In a comparison study, Renz et al found no T 1 W SI increase with a macrocyclic agent gadobutrol, whereas they also reported SI elevation in the DN with a linear agent, gadopentetate dimeglumine. Their study included pediatric patients with at least three injections of GBCAs.…”
Section: Discussionmentioning
confidence: 98%
“…A previous single case report in a pediatric patient who received 4 administrations of a linear GBCA (gadopentetate and possibly gadodiamide) described similar observations [22]. Gadolinium deposition seems to be class-dependent, as no brain MRI modification is visible in subjects who received several doses of macrocyclic agents [18,[23][24][25]. Nevertheless, after an average of 10 macrocyclic GBCA administrations, a SI increase has been quantitatively measured in the dentate nucleus and globus pallidus of 50 children [26].…”
mentioning
confidence: 70%
“…1 [15][16][17][18][19], showed a significant decrease in the time spent on the rotarod on day 3 in both GBCA-treated groups (gadoterate meglumine-treated group, p < 0.001 and gadodiamide-treated group, p < 0.001, by ANOVA followed by Bonferroni test) compared with that in the control group. ***p < 0.001…”
mentioning
confidence: 99%
See 1 more Smart Citation